Sustainable Batik Wastewater Treatment using Advanced PVDF/NiFe@SiO2 Nanocomposite Photocatalytic Membrane - Kusworo, Tutuk Djoko; Budiyono, Budiyono; Sumardiono, Siswo (Waste Technology, 2024)
The primary concern associated with the Batik industry lies in the presence of pollutant dyes that contribute to environmental contamination. Addressing this issue involves exploring various wastewater treatment methods, with membrane technology being a viable approach. In this study, a photocatalytic material, NiFe@SiO2, synthesized through the sol-gel technique, was incorporated into a PVDF membrane. Characterization results from SEM surface, indicated that the PVDF/NiFe@SiO2 membrane displayed superior characteristics compared to other membranes. The addition of the NiFe@SiO2 photocatalyst increased membrane porosity, hydrophilicity, water absorption capacity, and affinity towards water molecules. The PVDF/NiFe@SiO2 membrane exhibited enhanced performance in terms of permeate flux, pollutant rejection, stability, recyclability, and durability. Notably, the fabricated photocatalytic membrane demonstrated superior antifouling performance and flux recovery capability when operating under UV radiation. The study also delved into the influence of wastewater pretreatment on antifouling membrane performance. The modified membrane successfully reduced fouling levels on the membrane by enhancing FRR from ~70% to ~90%. This insight into how pretreatment affects the antifouling properties of wastewater opens avenues for innovative solutions and enhanced design strategies to improve the efficiency and sustainability of wastewater treatment processes. Future research endeavors could focus on maximizing the potential of the bentonite adsorbent in wastewater pretreatment and exploring the full capabilities of the NiFe@SiO2 photocatalyst in enhancing the photocatalytic and antifouling performance of the membrane.